2003
DOI: 10.1161/01.res.0000063424.28903.bb
|View full text |Cite
|
Sign up to set email alerts
|

Increased Superoxide Generation Is Associated With Pulmonary Hypertension in Fetal Lambs

Abstract: Abstract-Ligation of the ductus arteriosus in utero produces pulmonary hypertension and vascular remodeling in fetal and newborn lambs. However, the mechanisms producing these vascular changes are not well defined. Because reactive oxygen species (ROS) have been implicated as mediators of smooth muscle cell proliferation, we hypothesized that increased formation of ROS may be involved in the pathophysiology of pulmonary hypertension after in utero ductal ligation. Using ethidium fluorescence, we demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
189
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(209 citation statements)
references
References 43 publications
(41 reference statements)
13
189
3
3
Order By: Relevance
“…In a lamb model of PH of the newborn, it has been shown that the NADPH oxidase enzyme complex may contribute to proliferation of SMCs by producing increasing superoxide levels. 115,116 Moreover, the proliferative effect of endothelin 1 on fetal PASMCs is a consequence of increased generation of ROSs. 117 Regulation of the growth of PASMCs by the transcription factor GATA4 is inhibited by antioxidant serotonin via suppression of NADPH oxidase or monoamine oxidase A, further reinforcing the critical role of ROSs in altering signaling pathways involved in PH.…”
Section: Role Of Lysophosphatidic Acidmentioning
confidence: 99%
“…In a lamb model of PH of the newborn, it has been shown that the NADPH oxidase enzyme complex may contribute to proliferation of SMCs by producing increasing superoxide levels. 115,116 Moreover, the proliferative effect of endothelin 1 on fetal PASMCs is a consequence of increased generation of ROSs. 117 Regulation of the growth of PASMCs by the transcription factor GATA4 is inhibited by antioxidant serotonin via suppression of NADPH oxidase or monoamine oxidase A, further reinforcing the critical role of ROSs in altering signaling pathways involved in PH.…”
Section: Role Of Lysophosphatidic Acidmentioning
confidence: 99%
“…11,12 Scavenging by superoxide radicals may account in part for reduced NO bioactivity. 13 Increased superoxide production has been observed in experimental models of pulmonary hypertension, 14 and markers of oxida-tive stress are increased in patients with pulmonary hypertension. 15 Superoxide mediates pulmonary vasoconstriction 16 and stimulates pulmonary smooth muscle cell proliferation.…”
Section: See P 2022mentioning
confidence: 99%
“…NOS activity was determined by 14 C-arginine to 14 C-citrulline conversion with HPLC quantification as described. 24 Lung homogenates (400 g protein) were incubated for 30 minutes at 37°C in 500 L Krebs-HEPES buffer containing 14 C-arginine (2 L of 50 Ci/mL), FAD (10 mol/L), FMN (10 mol/L), and NADPH (1 mmol/L).…”
Section: Nos Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide is an oxygen free radical generated in pulmonary arteries by xanthine oxidase, NADPH-oxidase, or uncoupled eNOS in ECs [66]. Although, mechanism of ROS induction is not well-known, endothelin and angiotensin are found to activate NADPHoxidase in vascular SMCs [66][67][68]. Decreased availability of arginine, tetrahydrobiopterin, and heat shock protein-90, lead to uncoupling of eNOS and release of superoxide [68].…”
Section: Role Of Oxidant Stressmentioning
confidence: 99%